High-performance photodetectors and enhanced photocatalysts of two-dimensional TiO2 nanosheets under UV light excitation. Issue 15 (31st March 2016) - Yang, Jiao; Jiang, Yi-Lin; Li, Lin-Jie; Muhire, Elisée; Gao, Mei-Zhen
Abstract : Due to the large surface area-to-volume ratio and rapid electron transfer, 2D TiO2 nanosheets with ultrathin thicknesses are synthesized by using a bottom-up strategy and these nanosheet (NS)-based photocatalysts and photodetectors were explored for the first time. Abstract : Due to the large surface area-to-volume ratio and rapid electron transfer, two-dimensional (2D) TiO2 nanosheets with ultrathin thicknesses are synthesized by using a bottom-up strategy and these self-assembled nanosheet (NS)-based photocatalysts and photodetectors were explored for the first time. The influence of calcination temperature on microstructures and photocatalytic activity of TiO2 nanosheets were discovered and presented. The as-obtained TiO2 nanosheets were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Brunauer–Emmett–Teller (BET) analysis, Fourier transform infrared (FTIR) spectroscopy, UV-vis spectrophotometry, and X-ray photoelectron spectroscopy (XPS). The following heat treatment process induced phase evolution from rutile to anatase. The TiO2 nanosheets calcined at 500 °C exhibited the best activity for photo-degradation of organic dyes under UV light irradiation. The obtained photodetector exhibits excellent performance with a high photocurrent to dark current ratio and fast response and recovery times. Additionally, we demonstrated that the device may have potential applications in the future low-power optoelectronics system.